Involvement of Lyn and the atypical kinase SgK269/PEAK1 in a basal breast cancer signaling pathway - Croucher, David R; Hochgräfe, Falko; Zhang, Luxi; Liu, Ling; Lyons, Ruth J; Rickwood, Danny; Tactacan, Carole M; Browne, Brigid C; Ali, Naveid; Chan, Howard; Shearer, Robert; Gallego-Ortega, David; et al. (Cancer research (Chicago, Ill.), 2013)
Basal breast cancer cells feature high expression of the Src family kinase Lyn that has been implicated in the pathogenicity of this disease. In this study, we identified novel Lyn kinase substrates, the most prominent of which was the atypical kinase SgK269 (PEAK1). In breast cancer cells, SgK269 expression associated with the basal phenotype. In primary breast tumors, SgK269 overexpression was detected in a subset of basal, HER2-positive, and luminal cancers. In immortalized MCF-10A mammary epithelial cells, SgK269 promoted transition to a mesenchymal phenotype and increased cell motility and invasion. Growth of MCF-10A acini in three-dimensional (3D) culture was enhanced upon SgK269 overexpression, which induced an abnormal, multilobular acinar morphology and promoted extracellular signal-regulated kinase (Erk) and Stat3 activation. SgK269 Y635F, mutated at a major Lyn phosphorylation site, did not enhance acinar size or cellular invasion. We show that Y635 represents a Grb2-binding site that promotes both Stat3 and Erk activation in 3D culture. RNA interference-mediated attenuation of SgK269 in basal breast cancer cells promoted acquisition of epithelial characteristics and decreased anchorage-independent growth. Together, our results define a novel signaling pathway in basal breast cancer involving Lyn and SgK269 that offers clinical opportunities for therapeutic intervention.